2007
DOI: 10.1152/ajprenal.00229.2006
|View full text |Cite
|
Sign up to set email alerts
|

Origin of spontaneous activity in neonatal and adult rat bladders and its enhancement by stretch and muscarinic agonists

Abstract: This study examined the origin of spontaneous activity in neonatal and adult rat bladders and the effect of stretch and muscarinic agonists and antagonists on spontaneous activity. Rats were anesthetized and their bladders were excised, cannulated, and loaded with voltage- and Ca(2+)-sensitive dyes. Intracellular Ca(2+) and membrane potential transients were mapped using photodiode arrays in whole bladders, bladder sheets, or cross-section preparations at 37 degrees C. Intravesical pressure was recorded from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 31 publications
(31 reference statements)
4
111
1
Order By: Relevance
“…Treatment of those areas with BoNT/A might be sufficient enough to reduce detrusor contractions in NDO patients, regardless of the total amount of detrusor area covered. Experimental studies in neonate and spinal cord injured rats showed that spontaneous contractile activity originated in the urothelium-suburothelium near the bladder dome [23,24]. This spontaneous activity, unlike activity in normal adult rat bladders, is highly organized, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of those areas with BoNT/A might be sufficient enough to reduce detrusor contractions in NDO patients, regardless of the total amount of detrusor area covered. Experimental studies in neonate and spinal cord injured rats showed that spontaneous contractile activity originated in the urothelium-suburothelium near the bladder dome [23,24]. This spontaneous activity, unlike activity in normal adult rat bladders, is highly organized, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason eventually underlying these results might be areas of detrusor tissue, which are more important for detrusor contraction and increase of local reflex activity than other areas after spinal cord injury [23]. Treatment of those areas with BoNT/A might be sufficient enough to reduce detrusor contractions in NDO patients, regardless of the total amount of detrusor area covered.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the close proximity of urothelial cells to myofibroblasts and bladder nerves, the sensitivity of these cells to ATP (indicated by an ATP-induced increase in intracellular Ca 2+ in afferent neurons, urothelial cells and myofibroblasts), and the evidence for cell-cell coupling mediated by gap junctions provide support for a number of physical and chemical interactions that could influence bladder function. 25,39 Activation of P2Y or P2X receptors by ATP release during bladder distension could, therefore, have a role in autocrine and paracrine signaling throughout the urothelium. This hypothesis is supported by a study published in 2005, which found that urothelial-derived ATP release in the urinary bladder purportedly acts as a trigger for exocytosis-in part via autocrine activation of urothelial purinergic (P2X and P2Y) receptors.…”
Section: Role Of Different Receptors and Substances In Urothelial Funmentioning
confidence: 99%
“…The urothelium is known to release both ATP and ACh (19,41,73), and the submucosal space is richly innervated with nerve fibers that could also potentially release ATP and ACh (15,24,70). To determine whether mucosal phasic contractions were being driven by urothelial and/or neuronal release of ATP or ACh, we exposed mucosal tissue strips to atropine (20 M) to block muscarinic receptors, ␣,␤-methylene ATP (10 M) to desensitize and block P 2X purinergic receptors, or TTX (10 M) to block neuronal transmission.…”
Section: Morphology Of Mucosal Stripsmentioning
confidence: 99%